Chemical constituents and insecticidal activities of the essential oil from Alpinia blepharocalyx rhizomes against Lasioderma serricorne - Wang Ying (Journal of the Serbian Chemical Society, 2015)
The aim of this research was to determine the chemical constituents and toxicities of essential oil derived from Alpinia blepharocalyx rhizomes against the cigarette beetle, Lasioderma serricorne (Fabricius). Essential oil of A. blepharocalyx rhizomes was obtained from hydrodistillation and was investigated by Gas Chromatography-Mass Spectrometry (GC-MS). A total of 46 components of the essential oil of A. blepharocalyx rhizomes were identified. The principal compounds in A. blepharocalyx essential oil were camphor (23.13%), sabinene (11.27%), α-pinene (9.81%) and eucalyptol (8.86%) followed by camphene (8.05%), sylvestrene (5.61%) and α-phellandrene (5.00%). Among them, the four active constituents, predicted with a bioactivity-test, were isolated and identified as camphor, sabinene, α-pinene and eucalyptol. The essential oil of A. blepharocalyx possessed strong contact toxicity against the cigarette beetle with LD50 value of 15.02 μg adult-1, and also exhibited strong fumigant toxicity against L. serricorne adults with LC50 value of 3.83 mg L-1 air. The results indicate that the essential oil of A. blepharocalyx shows potential in terms of contact and fumigant toxicities against stored product insects.